Experimental and computational investigation of the endwall flow in a cascade of compressor blades - Carlson, James R. (Monterey, California. Naval Postgraduate School, 2012)
Approved for public release; distribution is unlimited === An investigation of the three-dimensional flow in a cascade of second-generation controlled-diffusion blades, which was as a result of the interaction of the endwall boundary layers with the blade profiles, is reported. Five-hole probe wake surveys were performed at various spanwise locations to determine the total pressure loss distribution. Downstream velocity vector information was also obtained from the five-hole probe surveys. Two-component laser-Doppler velocimetry (LDV) was used to characterize the flow in the inlet and wake regions. A numerical investigation of the flowfield was conducted using SWIFT, a computational fluid dynamics code developed by Dr. Roderick Chima of NASA Glenn Research Center. Experimental blade-surface pressure coefficients were compared with values predicted using SWIFT. Overall, good correlation between the five-hole probe and LDV measurement techniques was obtained; however, the CFD predictions did not match well with the experimental results, particularly at the midspan location of the blade where separation of the suction surface boundary layer occurred